What Is Bad From the Gander Is Bad From the Goose: Development and Validation of the Women's Objectification of Women Scale. (July 2020) - Parent, Mike C.; Garos, Sheila; Branscome, Emily; Piper, Margaret
Existing measures of experiences of sexualization and objectification of women focus on behaviors that men do toward women. However, women may also contribute to the objectification of other women. The aim of the present study was to develop the Women's Objectification of Women Scale (WOWS). Through a series of four studies using samples of college women and samples obtained through MTurk, we (a) established that existing measures of objectification focus on behaviors that men perform, (b) gathered qualitative data on women's experiences of objectification by women, (c) developed models of the WOWS using classical test theory methods and item response theory, and (d) subjected the WOWS to confirmatory factor analysis and validity testing. The WOWS is a psychometrically sound, brief assessment of women's experiences of objectification by other women and may help further research on women's interpersonal experiences as they pertain to body image concerns, mental health, and well-being.